A comparison of haemolytic responses in fore-foot and rear-foot distance runners. Issue 15 (2nd August 2016) - Caulfield, Stuart; McDonald, Kirsty A.; Dawson, Brian; Stearne, Sarah M.; Green, Ben A.; Rubenson, Jonas; Clemons, Tristan D.; Peeling, Peter
ABSTRACT: This study examined the haemolytic effects of an interval-based running task in fore-foot and rear-foot striking runners. Nineteen male distance runners (10 fore-foot, 9 rear-foot) completed 8 × 3 min repeats at 90% vVO2peak on a motorised treadmill. Pre- and post-exercise venous blood samples were analysed for serum haptoglobin to quantify the haemolytic response to running. Vertical ground reaction forces were also captured via a force plate beneath the treadmill belt. Haptoglobin levels were significantly decreased following exercise ( P = 0.001) in both groups (but not between groups), suggesting that the running task created a haemolytic stress. The ground reaction force data showed strong effect sizes for a greater peak force ( d = 1.20) and impulse ( d = 1.37) in fore-foot runners, and a greater rate of force development ( d = 2.74) in rear-foot runners. The lack of difference in haptoglobin response between groups may be explained by the trend for fore-foot runners to experience greater peak force and impulse during the stance phase of their running gait, potentially negating any impact of the greater rate of force development occurring from the rear-foot runners' heel strike. Neither type of runner (fore-foot or rear-foot) appears more susceptible to technique-related foot-strike haemolysis.